Uterine Torsion in an Elderly Woman Associated with Leiomyoma and Continuously Elevating Muscle Enzymes: A Case Study and Review of Literature - Oda, Hiroko (Case Rep Obstet Gynecol, 2020)
Uterine torsion is extremely rare in postmenopausal women. Total ischemia of the uterus may cause life-threatening conditions; hence, accurate diagnosis and surgical intervention are crucial. However, preoperative diagnosis is often challenging due to nonspecific clinical features and laboratory findings. We report a case of uterine torsion in a 73-year-old woman who presented with mild but gradually worsening intermittent abdominal pain. During a 5-day observation, repeated blood exams showed elevating serum muscle enzyme levels, lactate dehydrogenase (LDH), and creatinine kinase (CPK), in addition to nonspecific signs of inflammation. Computed tomography (CT) scans were obtained before and after the worsening of symptoms, which revealed changes in size and position of the enlarged uterus with a large leiomyoma, even within a 5-day interval. Based on these findings, the preoperative diagnosis was uterine torsion. Emergency surgery revealed a 540-degree torsion of the uterus at the cervix and uterine body junction. Total hysterectomy and bilateral salpingo-oophorectomy were performed. Plasma muscle enzyme levels normalized after surgery, and the patient recovered without complications. In conclusion, uterine torsion should be considered during differential diagnosis in elderly women with large leiomyoma, even when symptoms are mild. Elevating plasma muscle enzymes may be an indication of uterine torsion; hence, repeated laboratory works and CT scanning should be performed when symptoms progress. Comparison of CT images, taken before and after the worsening of symptoms, may also be relevant for diagnosis. Since uterine torsion may cause rapid deterioration and become life-threatening, early diagnosis and surgical intervention are crucial to avoid serious complications.